Paper making process from coconut coir as an alternative to wood / Khiril Nizam Husin - Husin, Khiril Nizam (2013)
The purpose of this study was to identify whether the coconut coir can be replaced wood as the main material to produce paper in the future. Paper and paper-based products are important in our lives. They are use in all our dealings whether in the office, supermarket, and restaurant or even use the bathroom. Paper also is one of the important things and it is used extensively in the offices. In 1996, Malaysia has own paper usage and has reached almost two million metric tons. Because of the widespread use of paper throughout the world, it causes the use of wood in large quantities for the production of paper. This has caused problems in supplying paper at this time. Therefore, the present research has been focusing towards finding the raw materials that is capable for replacing wood as the main material. Hence, this project is done in order to test whether coconut fiber (fiber) could potentially replace the use of wood in paper making. A research has been done before about coir fiber. Coconut coir contains cellulose fiber which is high enough and it can be used as pulp manufacturing. It can also be used in the manufacture of composite materials consisting of a combination of coir fiber paper pulp and pulp formation of HVS. Furthermore fiber pulp fibers having the highest levels of alpha cellulose mixed with pulp from waste paper used as raw material in the manufacture of composite paper. Then form a composite paper features such as strong pull, the ability to absorb ink, writing ability and endurance has been tested.